The System and Mechanism in Managing Area-Based Collaborative Research for Development, Rajamangala University of Technology Suvarnabhumi - Boonlertnirun, Kitti; Leasen, Suthisa; Thongrak, Phakhwan; Rattanabanlue, Aekchai; Songthong, Montri; Nawatnatee, Tharanee (Area Based Development Research Journal, 2018)
The system and mechanism in managing research of Rajamangala University of Technology Suvarnabhumi vitally contributes to a higher education institution for community engagement. This study aims to 1) develop the system and mechanism in managing area-based collaborative research; 2) develop human resources as research coordinators and researchers; and 3) build knowledge and innovation relevant to the target areas. The system and mechanism in research management was designed as an action research by establishment of research and innovations for society center to support area-based research. Achievement motivation was based to manage the research programs and the projects. The results indicated the importance of good management at all stages of research conduct. That is, the upstream process reflects an analysis of the problem context and the demand for development of areas and research problems conforming to the demand, whereas the midstream process contains the development of researchers and research coordinators to gain knowledge, to improve attitude towards research for community, and to design the community-based research mechanism. At the same time, the downstream process supports the researchers for their academic work publication and for networking management on area-based development mechanism. All these lead to Interdisciplinary team-based research in which the researchers share common goals under strong achievement motivation resulting in academically accepted research that can be applied to the target community. Having continuously conducted research projects for 3 years since 2015 in Phra Nakhon Si Ayutthaya, Suphanburi and Nonthaburi province aiming to stabilizing in careers from community resources, the institute has run 14, 17, 17 projects in each province respectively with 55-59 researchers including 45-49 novice researchers. As for the first and second year of the research programs, 20 scholarly articles were published in academic journals. In addition, there were community exhibitions incorporated with provincial network. The community actively participates in academic activities and utilizes the knowledge from the research in various aspects including development planning in promotion of career groups, community-based tourism management, as well as grouping of community national resource and water conservation.